Six Keys for Delibes (XXI Century. Spanish Literature and Culture, 2003)
The author goes through the professional and literary trajectory of the writer from Valladolid, parallel to the evolution of post-war literature. It also studies the influence his journalist activity had in his novels.
Keywords: Miguel Delibes; Social realism; narrative; journalism; transition; post-war